Silent Messengers The Circulation of Material Objects of Knowledge in the Early Modern Low Countries - Dupré, Sven (2011)
This book speaks about a world of mute objects ranging from plant bulbs, divining rods, and archeological findings to drawn, painted or printed images. It describes the functions of these objects as ambiguous and polyvalent carriers of knowledge, and analyzes the ways in which networks of scholars, craftsmen, mathematicians, anatomy professors or merchants active in the Low Countries attributed new meanings to them. The book treats of a period in which cities like Antwerp and Amsterdam were nodal points in the international exchange of goods, news, and skills.